2008
DOI: 10.2139/ssrn.1138244
|View full text |Cite
|
Sign up to set email alerts
|

Are Young French Jobseekers of Ethnic Immigrant Origin Discriminated Against? A Controlled Experiment in the Paris Area

Abstract: This study uses the findings of a correspondence testing in order to assess the potential discrimination at job access level against young people of ethnic origin from the underprivileged suburbs of the Paris area (Ile-de-France

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
0
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 12 publications
(7 reference statements)
6
70
0
11
Order By: Relevance
“…It would be necessary carry out new tests for the existence of discrimination in order to confirm their level of generality. Nevertheless, our findings confirm those from previous studies on other professions or occupations, which consistently concluded that there exists a marked effect of residence (Duguet et al [2010], L'Horty et al [2012], Small et al [2013]). Our findings dovetail with the point that the applicant`s place of residence sends a signal that may capture a combined effect of the department, the town or municipality, and the neighborhood.…”
Section: Discussionsupporting
confidence: 92%
“…It would be necessary carry out new tests for the existence of discrimination in order to confirm their level of generality. Nevertheless, our findings confirm those from previous studies on other professions or occupations, which consistently concluded that there exists a marked effect of residence (Duguet et al [2010], L'Horty et al [2012], Small et al [2013]). Our findings dovetail with the point that the applicant`s place of residence sends a signal that may capture a combined effect of the department, the town or municipality, and the neighborhood.…”
Section: Discussionsupporting
confidence: 92%
“…A rst piece of evidence comes from audit studies that show that African workers have a lower chance of being interviewed, all else being equal (see, e.g., Cediey and Foroni (2006); Duguet et al (2010)). Very few studies use survey data and document the over-exposure of African workers to unemployment risk (see, e.g., Aeberhardt et al (2010) ; Algan et al (2010)).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the net discrimination rate is comparable to previous research on rental housing discrimination against ethnic minorities in Europe, and in some cases even higher. 4,5,6,7,8,9,10,11,12,13,14 The argument by Gordon and Rosenblum 3 that discrimination against individuals with a visual impairment might be compared to discrimination based on other criteria seems defensible, at least in order of magnitude. Our results confirm that the discrimination of individuals with a visual impairment is a tangible problem.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…An obvious form of social exclusion is discrimination on the labour and housing markets. Although there are numerous empirical studies in Europe about discrimination on the basis of ethnicity 4,5,6,7,8,9,10,11,12,13,14 , gender 4,7,8,15 and sexual orientation 16,17,18,19 , research into discrimination of people with a disability is scarce. A meta-analysis of discrimination research conducted since 2000 showed that there were only four studies on disability 20 : two studies on housing discrimination in the United States 21,22 , one study on hiring discrimination in Scotland 23 , and one study on product market discrimination in the United States 24 .…”
Section: Introductionmentioning
confidence: 99%